Beneficial effects of Rifaximin in post‐infectious irritable bowel syndrome mouse model beyond gut microbiota. Issue 2 (26th January 2018) - Jin, Yu; Ren, Xiaoyang; Li, Gangping; Li, Ying; Zhang, Lei; Wang, Huan; Qian, Wei; Hou, Xiaohua
Abstract: Background and Aims: Rifaximin is a minimally absorbed antibiotic, which has shown efficacy in irritable bowel syndrome (IBS) patients. However, the mechanism on how it effects in IBS is still incompletely defined. In this study, Trichinella spiralis ‐infected post‐infectious (PI) IBS mouse model was used, to assess the action of rifaximin on visceral hypersensitivity, barrier function, gut inflammation, and microbiota. Methods: Post‐infectious IBS model was established by T. spiralis infection in mice. Rifaximin were administered to PI‐IBS mice for seven consecutive days. The abdominal withdrawal reflex and threshold of colorectal distention were employed to evaluate visceral sensitivity. Smooth muscle contractile response was recorded in the organ bath. Intestinal permeability was measured by Ussing chamber. Expression of tight junction protein and cytokines were measured by Western blotting. Ilumina miseq platform was used to analyze bacterial 16S ribosomal RNA. Results: Post‐infectious IBS mice treated with rifaximin exhibited decreased abdominal withdrawal reflex score, increased threshold, reduced contractile response, and intestinal permeability. Rifaximin also suppressed the expression of interleukin‐12 and interleukin‐17 and promoted the expression of the major tight junction protein occludin. Furthermore, rifaximin did not change the composition and diversity, and the study reavealed that rifaximin had a tiny effect on the relative abundance of Lactobacillus and Bifidobacterium in this PI‐IBS model. Conclusions: Rifaximin alleviated visceral hypersensitivity, recovered intestinal barrier function, and inhibited low‐grade inflammation in colon and ileum of PI‐IBS mouse model. Moreover, rifaximin exerts anti‐inflammatory effects with only a minimal effect on the overall composition and diversity of the gut microbiota in this model.